Удмурты: историческая литература / составитель Г. Г. Грязев - Грязев Георгий Геннадьевич (Удмуртия, 2022)
Экземпляры: КО (2023) / Инвентарный номер: 58598 / Цена: / Сис.шифр: К63.5(2Рос.Удм) / Авт.знак: У 30 / ГРНТИ: 03.23 / ББК: 63.5(2=664.1)